#### Answer

$x=\left\{ -3,3 \right\}$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To solve the given equation, $
-4x^2+36=0
,$ simplify first by dividing both sides by $GCF.$ Then express the equation in $x^2=c$ form and get the square root of both sides (Square Root Principle).
$\bf{\text{Solution Details:}}$
Dividing both sides by $-4$, the equation above is equivalent to
\begin{array}{l}\require{cancel}
x^2-9=0
\\\\
x^2=9
.\end{array}
Taking the square root of both sides (Square Root Principle), the equation above is equivalent to
\begin{array}{l}\require{cancel}
x=\pm\sqrt{9}
\\\\
x=\pm3
.\end{array}
Hence, $
x=\left\{ -3,3 \right\}
.$